Maximal Oxygen Uptake Is Achieved in Hypoxia but Not Normoxia during an Exhaustive Severe Intensity Run - Black, Matthew I.; Potter, Christopher R.; Corbett, Jo; Clark, Cain C. T.; Draper, Stephen B. (Frontiers in Physiology, 2017)
Highly aerobically trained individuals are unable to achieve maximal oxygen uptake ( O2max) during exhaustive running lasting 2 min, instead O2 plateaus below O2max after 1 min. Hypoxia offers the opportunity to study the O2 response to an exhaustive run relative to a hypoxia-induced attenuation in O2max. The aim of this study was to explore whether there is a difference in the percentage of O2max achieved (during a 2 min exhaustive run) in normoxia and hypoxia. Fourteen competitive middle-distance runners (normoxic O2max 67.0 ± 5.2 ml.kg-1.min-1) completed exhaustive treadmill ramp tests and square-wave tests in normoxia and hypoxia (FiO2 0.13). The O2 data from the square-wave tests were modelled using a mono-exponential function. End-exercise normoxic square-wave O2 was less than normoxic O2max (86 ± 6% ramp, P < 0.001). During the hypoxic square-wave test, hypoxic O2max was achieved (102 ± 8% ramp, P = 0.490). The phase II time constant was greater in hypoxia 12.7 ± 2.8 s vs. 10.4 ± 2.6 s (P = 0.029). The results further support findings demonstrating that highly aerobically trained individuals cannot achieve O2max during exhaustive severe intensity treadmill running in normoxia. However, these individuals are able to achieve the lower O2max in hypoxia despite a slightly slower O2 response in this condition.